Dampak Kualitas Layanan Dan Kinerja Keuangan Terhadap Keinginan Migrasi Nasabah Bank Syariah Di Jawa Tengah - ardiansah, muhammad noor (Jurnal Sains Ekonomi dan Perbankan Syariah, 2011)
This researchâs aim to examined impact of banking services quality and financial performance toward shariah bankâs customer migration intention. Respondent of this study were shariah bankâs customer at 7 big cities in Central Java, who asked to perform the questionnaire. Regression analysis used to examine the hypothesis. Result show that intention of bankâs customer to migration was influence by banking services quality and financial performance, significantly. Especially financial performance determinant : operational expenses and revenue ratio and assets growth. This results support empirically research of Ardiansah (2005), and Derina and Makaliwe (2006), that shariah banking behavior who more rational and financial aspects orientation should take banking services quality and financial performance that profitability as expected decision